INTERACT '93 and CHI '93 Conference Companion on Human Factors in Computing Systems - CHI '93 1993
DOI: 10.1145/259964.260149
|View full text |Cite
|
Sign up to set email alerts
|

Studying the movement of high-tech Rodentia

Abstract: This study compares seven input devices (mouse, touchsereen, two trackba.lls, mousepen, touchp@ and joystick) performing a star tracing task. Along with the device comparisons, the diffemtce between moving with the selector button pressed (dragging) or with the button released (pointing) is examined. Recent work has found that dragging is slower and more error prone than pointing when using a mouse, stylus or trackball [1~,3]. In the present study, 28 subjects used all seven input deviees for boti dragging and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…This task dependency on the performance of the devices is best illustrated by the performance difference of the touchween in a prior study [1] and the current study. It moved from fast to last!…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This task dependency on the performance of the devices is best illustrated by the performance difference of the touchween in a prior study [1] and the current study. It moved from fast to last!…”
Section: Discussionmentioning
confidence: 54%
“…Four of the devices (mouse, mousepen, trackball, and touchscreen) were chosen based on their strong performance in a previous experiment [1]. Since the fiit experiment used a simple laboratory task, their inclusion in the cummt study will directly address the impact which the experimental task has on device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies expanded the knowledge on the usability of various input devices for 2D pointing tasks (e.g. [6,8,10,16]). Common observations from the various studies are that isotonic devices such as touchscreens, tablets and mice perform best and that position control is superior to rate control.…”
Section: Related Workmentioning
confidence: 99%
“…Previous work has suggested that a touchscreen may perform better than a touchpad [4] and at least as well as a mouse [7]. While we did not perform rigorous testing with the touchscreen, we tried to discover any performance issues associated with the stylus and to understand participants' preferences for the touchscreen compared to their PC's pointing device.…”
Section: The Stylusmentioning
confidence: 99%